Roni Horn - when I breathe, I draw - White, Michelle 1979- (The Menil Collection, 2019)
Describing drawing as her "primary activity," for over thirty years, Roni Horn (b. 1955) has created innovative and experimental works on paper marked by both conceptual and technical complexity. This carefully curated survey of the artist's drawings from the early 1980s through 2016 explores works revolving around the mutability of identity and the fragility of place, time, and language; it also delves into Horn's unique approach to mark-making and her process of cutting up and reassembling words and images. With sumptuous illustrations, this catalogue features an insightful look at Horn's large-scale-sometimes over ten feet tall-works on paper; the artist's series of cadmium red drawings; and her cut-and-pasted word drawings that combine well-known literary texts by Gertrude Stein and William Shakespeare with colloquial expressions
Published in conjunction with a exhibition ... organized by The Menil Collection, part one February 15-May 5, 2019, part two June 7-September 1, 2019
Keywords: Horn, Roni -- 1955-; Horn, Roni / 1955- / Exhibitions; Art, Modern / 21st century / Exhibitions; Bildband; Ausstellungskatalog -- The Menil Collection -- 15.02.2019-05.05.2019 -- Houston, Tex.; Ausstellungskatalog -- The Menil Collection -- 07.06.2019-01.09.2019 -- Houston, Tex.